Salivary oxytocin in adolescents with conduct problems and callous-unemotional traits - Levy, Tomer; Bloch, Yuval; Bar-Maisels, Meytal; Gat-Yablonski, Galia; Djalovski, Amir; Borodkin, Katy; Apter, Alan (European child & adolescent psychiatry, 2015)
Callous-unemotional (CU) traits correlate with the severity and prognosis of conduct disorder in youth. The neuropeptide oxytocin (OT) has been linked to prosocial behaviors, including empathy and collaboration with others. This study discusses a possible role for OT in the biology of delinquent behavior. We hypothesized that in delinquent youth OT secretion will correlate with the severity of conduct problems and specifically with the level of CU traits. The study group included 67 male adolescents (mean age 16.2 years) undergoing residential treatment, previously assessed by an open clinical interview and history for the psychiatric diagnosis. Staff based Inventory of Callous-Unemotional traits for psychopathy and Strength and Difficulties Questionnaire were administered, and patients’ medical and social personal files were systematically coded for previous history of antisocial acts using the Brown-Goodwin Questionnaire. Salivary OT was assayed by ELISA. Salivary OT levels were inversely correlated with conduct problems severity on Strength and Difficulties Questionnaire ( r = −0.27; p ≤ 0.01). Recorded history of antisocial acts did not correlate with current OT levels. Odds ratio (OR) for significant CU traits among subjects with conduct problems was increased in low-OT (OR = 14, p ≤ 0.05) but not in high-OT subjects (OR = 6, p ≥ 0.05). Children with conduct problems and low levels of salivary OT are at risk for significant CU traits. These results suggest a possible role for salivary OT as a biomarker for CU traits and conduct problems severity.